2015
DOI: 10.1080/15350770.2015.1058212
|View full text |Cite
|
Sign up to set email alerts
|

Developing the Ideal Grandparent Scale: Initial Validity and Reliability Tests

Abstract: Focus groups were conducted with 33 community dwelling, urban and rural, custodial grandparents to explore their willingness to comply with a behavioral intervention targeting improving their well-being and financial management. Most participants were African American (91%), female (79%) and middle-aged. Major themes included: 1) inability to access social services; 2) legal assistance; 3) emotional well-being; 4) problems related to the parents of grandchildren; and 5) identification of structured activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 66 publications
(29 reference statements)
5
24
0
Order By: Relevance
“…Grandchildren’s primary expectation of their grandparents is that grandparents convey that they enjoy spending time with their grandchildren (Kennedy, 1990), which coincides with the finding that positivity is used most frequently by grandparents. Grandchildren also believe ideal grandparents are family oriented (Mansson, 2015), important members of the family (in particular the parent–child relationship) who should offer grandchildren advice and support (Kennedy, 1990; Soliz, 2008), which reflects the prevalence of networks and advice relational maintenance behaviors in this study. To a lesser degree, grandchildren believe their grandparents should assist with tasks and resolve problems (Kennedy, 1990), which taps into the tasks and conflict management behaviors (Stafford et al., 2000).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Grandchildren’s primary expectation of their grandparents is that grandparents convey that they enjoy spending time with their grandchildren (Kennedy, 1990), which coincides with the finding that positivity is used most frequently by grandparents. Grandchildren also believe ideal grandparents are family oriented (Mansson, 2015), important members of the family (in particular the parent–child relationship) who should offer grandchildren advice and support (Kennedy, 1990; Soliz, 2008), which reflects the prevalence of networks and advice relational maintenance behaviors in this study. To a lesser degree, grandchildren believe their grandparents should assist with tasks and resolve problems (Kennedy, 1990), which taps into the tasks and conflict management behaviors (Stafford et al., 2000).…”
Section: Discussionmentioning
confidence: 93%
“…The fact that the grandchildren reported that openness was used least frequently by their grandparents is initially peculiar because grandchildren perceive trustworthy grandparents as ideal (Mansson, 2015). However, it is possible that grandparents portray their GP-GC relationship feelings through their actions, such as giving gifts and offering assistance while being positive and family oriented, which may limit the need to overtly discuss their GP-GC relationship feelings.…”
Section: Discussionmentioning
confidence: 99%
“…This tool may help practitioners to get a better understanding of the grandparent-grandchild relationship and of young adult grandchildren's expectations toward their grandparents. In line with previous research, Mansson developed the IGS with reference to different facets of grandchildren's perceptions of their relationship with their grandparent (i.e., caring, social support, emotional closeness, shared family identity, affection in the grandparent-grandchild relationship) that may guide their expectations about the ideal grandparent (Mansson 2015).…”
Section: The Ideal Grandparent Scale (Igs)mentioning
confidence: 94%
“…de Dias and Silva (2003) investigated college students' representations of the grandparent and outlined that the ideal grandparent should love and care for their grandchildren and be open to communication. Then, Mansson (2015) developed the IGS by selecting possible items from the literature and by asking young adults which items could be applied to the ideal grandparent. High scores at the IGS correspond to the perception of the grandparent as ideal.…”
Section: The Ideal Grandparent Scale (Igs)mentioning
confidence: 99%
See 1 more Smart Citation